Esterase mediated pyrethroid resistance in Rhipicephalus microplus ticks collected from north-western Himalayas - GODARA, R; KATOCH, R; YADAV, A; NAZIM, KAIFA; SOFI, OMER MOHI U DIN; VERMA, P K (The Indian Journal of Animal Sciences, 2022)
Larval packet test (LPT) was used to evaluate resistancestatus against deltamethrin and cypermethrin in R. microplusticks collected from 8 districts of Jammu region. Resistanceagainst deltamethrin was detected at level 1 in three isolates,level 2 in two isolates and level 3 in one isolate while twoisolates were found susceptible. Four isolates were foundresistant to cypermethrin whereas, other four isolates weresusceptible. Quantitative analysis of general esteraseactivity revealed a range of 2.466±0.29 to 8.908±1.68 and1.279±0.22 to 5.793±1.24 μmol/min/mg protein for α- andβ-esterase activity, respectively. Multiple pairwisecomparisons of the mean values with susceptible fieldisolate revealed significant elevated levels of both α- andβ-esterases in Jammu isolate having highest RFs to bothdeltamethrin and cypermethrin. It can be concluded thatthe resistance against SPs has developed in R. microplusticks of north-western Himalayan region, India and esterasesplay a significant role in conferring the SPs resistance.